ANALISIS KESESUAIAN TANGGA DARURAT PADA GEDUNG A DI UNIVERSITAS BALIKPAPAN - Yuliana, Lina; Mappangile, Andi Surayya; Amiricano, Baramega (IDENTIFIKASI, 2021)
Occupational safety and health procedures in a building are very important, especially in high-rise buildings, because a high-rise building has unpredictable risks, for example in the event of an earthquake or fire. Some of the Balikpapan University Building A buildings have been equipped with emergency stairs, but their utilization is not optimal. So that the security and safety of the emergency stairs is still far from the standard for the function of the campus building. This can be seen from the absence of evacuation signs from each floor on the emergency stairs. The research objectives are (1) General To determine the suitability of the emergency stairs in Building A, University of Balikpapan. (2) Specifically to find out the completeness of the emergency stairs of Balikpapan University Building A. This research was conducted using a qualitative descriptive method in which the research results were described, analyzed and then drawn conclusions in finding conformity based on SNI 03-1746-2000. The results of the study found that the physical condition of the emergency stairs in Building A did not meet the requirements of the standard size and completeness of the means of exiting the emergency stairs, including emergency power sources, emergency lights, smoke control systems, emergency communications, openings for rescue routes, directions. egress and directional sign lighting. The conclusion is based on the results of the overall percentage data on the 1st floor to the 5th floor with an average value of 70% which is included in the criteria value between 50-80% in the "Enough" category for the physical condition of the emergency stairs in Building A. Keywords : A, Emergency, Building, Suitability, Stairs.